Interventional Treatment of Access Site Complications During Transfemoral TAVI: A Single Center Experience - Thieme, Marcus; Moebius-Winkler, Sven; Franz, Marcus; Baez, Laura; Schulze, Christian P.; Butter, Christian; Edlinger, Christoph; Kretzschmar, Daniel (Frontiers in Cardiovascular Medicine, 2021)
Introduction: Transcatheter aortic valve implantation (TAVI) has rapidly developed over the last decade and is nowadays the treatment of choice in the elderly patients irrespective of surgical risk. The outcome of these patients is mainly determined not only by the interventional procedure itself, but also by its complications. Material and Methods: We analyzed the outcome and procedural events of transfemoral TAVI procedures performed per year at our institution. The mean age of these patients is 79.2 years and 49% are female. All the patients underwent duplex ultrasonography of the iliac arteries and inguinal vessels before the procedure and CT of the aorta and iliac arteries. Results: Transfemoral access route is associated with a number of challenges and complications, especially in the patients suffering from peripheral artery disease (PAD). The rate of vascular complications at our center was 2.76% (19/689). Typical vascular complications (VC) include bleeding and pseudoaneurysms at the puncture site, acute or subacute occlusion of the access vessel, and dissection or perforation of the iliac vessels. In addition, there is the need for primary PTA of the access pathway in the presence of additional PAD of the common femoral artery (CFA) and iliac vessels. Balloon angioplasty, implantation of covered and uncovered stents, lithoplasty, and ultrasound-guided thrombin injection are available to treat the described issues. Conclusion: Interventional therapy of access vessels can preoperatively enable the transfemoral approach and successfully treat post-operative VC in most of the cases. Training the heart team to address these issues is a key focus, and an interventional vascular specialist should be part of this team.